2012
DOI: 10.1186/1479-5868-9-12
|View full text |Cite
|
Sign up to set email alerts
|

Can physical activity reduce excessive gestational weight gain? Findings from a Chinese urban pregnant women cohort study

Abstract: BackgroundExcessive gestational weight gain (GWG) poses negative impact on mothers and their children. It is important to understand the modifiable lifestyle factors associated with excessive GWG during pregnancy to guide future public health practice.AimTo investigate the association between physical activity during pregnancy and GWG of Chinese urban pregnant women.MethodsA pregnant women cohort was established between 2005 and 2007 in Changzhou, China. Physical activity levels of pregnant women were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
0
8

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(108 citation statements)
references
References 21 publications
7
93
0
8
Order By: Relevance
“…Similar recommendations have been proposed in Canada [8], Denmark [9], and the United Kingdom [10]. However, most of the studies used to develop those guidelines involved Caucasian women [11,12]; only a few involved Asian populations, [13], and there is no physical activity guideline for pregnant women in China.…”
Section: Objectivesmentioning
confidence: 76%
See 1 more Smart Citation
“…Similar recommendations have been proposed in Canada [8], Denmark [9], and the United Kingdom [10]. However, most of the studies used to develop those guidelines involved Caucasian women [11,12]; only a few involved Asian populations, [13], and there is no physical activity guideline for pregnant women in China.…”
Section: Objectivesmentioning
confidence: 76%
“…A study of 862 pregnant Chinese women found that [50 % of participants experienced excessive weight gain during pregnancy [13]. The rates of macrosomia and cesarean section in urban Chinese areas have increased significantly [15,16].…”
Section: Objectivesmentioning
confidence: 99%
“…Of these, 7 were focused on pregnancy outcomes including gestational weight gain (GWG) and maternal depression [12, 30, 34, 40, 44–46], 5 on metabolic outcomes [10, 36, 44, 47, 49], and 5 on infant outcomes [12, 31, 32, 39, 49]. …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Jiang et al [20] showed that PA levels during pregnancy, as well as pre-pregnancy BMI are inversely associated with gestational weight gain. Using pedometry to measure PA, they showed that the sedentary group (<5 000 steps per day) gained 1.45 kg (8% of the total GWG for the sedentary group) more weight during the last two trimesters of pregnancy than the active group (>10 000 steps per day).…”
Section: The Role Of Physical Activity In Pregnancymentioning
confidence: 87%
“…Using pedometry to measure PA, they showed that the sedentary group (<5 000 steps per day) gained 1.45 kg (8% of the total GWG for the sedentary group) more weight during the last two trimesters of pregnancy than the active group (>10 000 steps per day). [20] In addition, a recent review has highlighted the beneficial effect of PA in reducing the risk of pre-eclampsia, [21] possibly via its role in weight management.…”
Section: The Role Of Physical Activity In Pregnancymentioning
confidence: 99%